The Role of the Medical Certificate in the Judicial Practice - Kouchida, Tahar; Elwafi, Said (Journal of Legal Studies and Researches, 2023)
This study aims to ascertain importance of the medical certificate in the judicial work as evidence of denial or proof of the doctor's findings following his examination of the sick person or the corpse. Perhaps the most important conclusion is that the Algerian legislator did not address the guidelines governing the medical certificate in clear terms especially in editing it or criminalizing its forgery.